2022
DOI: 10.1101/2022.02.17.22271140
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of mHealth interventions on psychological issues experienced by women diagnosed with breast cancer receiving chemotherapy: A systematic review and meta-analysis

Abstract: Background:  A range of psychological issues often accompany breast cancer chemotherapy. Owing to their ubiquity, mobile phones have been used to deliver supportive interventions that address these issues. However, we currently lack sufficient evidence to guide the design of such interventions.  Aim:  To analyse and synthesise available evidence on the effectiveness of mobile-phone-based (mHealth) interventions in alleviating the psychological issues experienced by women receiving chemotherapy for breast can… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Subgroup analyses showed that these app-based interventions were effective with durations of <3 months but not with a duration of 3 to 12 months (SMD=−0.25, 95% CI −0.51 to 0.02; P=.07; I 2 =53%). When studies were grouped by type of cancer, 46% (6/13) of the studies involved breast cancer survivors [21][22][23]43,47,48], and mHealth app interventions did not alleviate depression in these survivors (SMD=−0.11, 95% CI −0.27 to 0.06; P=.21). Subgroup analyses according to intervention theory revealed that cognitive behavioral theory-based interventions could effectively relieve depression in cancer survivors (SMD=−0.75, 95% CI −1.42 to 0.09; P=.03), but there was high heterogeneity.…”
Section: Effects On Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subgroup analyses showed that these app-based interventions were effective with durations of <3 months but not with a duration of 3 to 12 months (SMD=−0.25, 95% CI −0.51 to 0.02; P=.07; I 2 =53%). When studies were grouped by type of cancer, 46% (6/13) of the studies involved breast cancer survivors [21][22][23]43,47,48], and mHealth app interventions did not alleviate depression in these survivors (SMD=−0.11, 95% CI −0.27 to 0.06; P=.21). Subgroup analyses according to intervention theory revealed that cognitive behavioral theory-based interventions could effectively relieve depression in cancer survivors (SMD=−0.75, 95% CI −1.42 to 0.09; P=.03), but there was high heterogeneity.…”
Section: Effects On Depressionmentioning
confidence: 99%
“…Although several systematic reviews have addressed the psychological impact of teleinterventions on cancer survivors [21][22][23][24], contradictory results remain. A meta-analysis that included 20 telehealth interventions found that the interventions improved patients' QOL and self-efficacy and reduced depression, distress, and perceived stress.…”
Section: Introductionmentioning
confidence: 99%
“…Several forms of telehealth have been used for the last several years in the area of oncology, and specifically breast cancer. mHealth apps have shown effectiveness in improving mood, symptom interference, self-efficacy, self-esteem, and emotional functioning [ 4 ]. mHealth apps provide education and improve health literacy [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%